Pelatihan Respectfull Mind untuk Mengembangkan Karakter Respek Mahasiswa - Nila Zaimatus Septiana (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2019)
This research is based on social phenomena that occur in the world of education, especially those relating to respect. Respectful mind is one of the ability to think that is important for the future and needs to be developed in the world of education, because it is related to ethical and moral problems and interpersonal relationships. This study aims to test the effectiveness of respectful mind training in developing the character of respect for first-year students. The method used in this research is quantitative with pre-experimental research, research design using one group pretest-posttest. The subjects of this study were first-year students, the subject was taken by using purposive sampling technique. Furthermore, the instruments used in this study include the training manual of respectfull mind and the main measurement instrument is respect questionnaire. Analysis of the data used in this study is a nonparametric statistical test that is Wilcoxon sign rank test. The results showed through statistical tests showed a significance level of 0.005 <0.05 which means that Ho was rejected, and respectfull mind training can improve student’s respect.